Hematopoietic Gene Expression Regulation Through m6A Methylation Predicts Prognosis in Stage III Colorectal Cancer - Zhou, Zheng; Mo, Shaobo; Gu, Ruiqi; Dai, Weixing; Zou, Xinhui; Han, Lingyu; Zhang, Long; Wang, Renjie; Cai, Guoxiang (Frontiers in Oncology, 2020)
Background: Methylation of N6 adenosine (m6A) plays important regulatory roles in diverse biological processes. The purpose of this research was to explore the potential mechanism of m6A modification level on the clinical outcome of stage III colorectal cancer (CRC). Methods: Gene set variation analysis (GSVA) and gene set enrichment analysis (GSEA) were adopted to reveal the signal pathway which was most likely affected by m6A methylation. The Linear models for microarray data (LIMMA) method and the least absolute shrink‐age and selection operator (LASSO) Cox regression model were used to identify the signature. Then, the multi-gene signature was validated in GSE14333 and the Cancer Genome Atlas (TCGA) cohort. Finally, two nomograms were set up and validated to predict prognosis of patients with stage III CRC. Results: The hematopoietic cell lineage (HCL) signaling pathway was disclosed through GSEA and GSVA. Seven HCL-related genes were determined in the LASSO model to construct signature, with AUC 0.663, 0.708, and 0.703 at 1, 3, and 5 years, respectively. Independent datasets analysis and stratification analysis indicated that the HCL-related signature was reliable in distinguishing high- and low-risk stage III CRC patients. Two nomograms incorporating the signature and pathological N stage were set up, which yielded good discrimination and calibration in the predictions of prognosis for stage III CRC patients. Conclusions: A novel HCL-related signature was developed as a predictive model for survival rate of stage III CRC patients. Nomograms based on the signature were advantageous to facilitate personalized counselling and treatment in stage III CRC.